Las medidas de prevención en las empresas y su incidencia en los accidentes de trabajo.Quevedo - Macías Yagual, Nelly América (2015)
Chapter I deals with everything related to the introduction, the problematization, several general principles of labor law throughout history, the formulation and definition of the problem, the rationale, objectives, assumptions, variables, resource use, materials used, budget and several comments of the problems investigated. In Chapter II relationship becomes the Theoretical background and research Marco, the merits respect on the historical evolution, definitions, general notions of work through different periods of history, doctrines on Labor Law, judgment issued by the Constitutional Court of Ecuador, study and analysis of comparative law, and several comments regarding the issues. Chapter III describes the methods used in research, such as inductive, deductive , analytical , historical and quantitative as well as the research design , population and sample, techniques and tools used and the method of data for use in research, and several comments. In this Chapter IV contains the analysis and interpretation of results, the questions posed to and driving and driven to labor claims, citizenship, legal professionals, testing the hypothesis, the research report and several comments. In Chapter V consist conclusions and recommendations. In Chapter VI refers to the proposal, justification, synthesis of diagnosis, the general and specific objectives, description of the proposal.